Dyadic Business Relationships within a Business Network Context - Anderson, James C.; Håkansson, Håkan; Johanson, Jan (Journal of Marketing, 1994)
In business-to-business settings, dyadic relationships between firms are of paramount interest. Recent developments in business practice strongly suggest that to understand these business relationships, greater attention must be directed to the embedded context within which dyadic business relationships take place. The authors provide a means for understanding the connectedness of these relationships. They then conduct a substantive validity assessment to furnish some empirical support that the constructs they propose are sufficiently well delineated and to generate some suggested measures for them. They conclude with a prospectus for research on business relationships within business networks.